THE IMPACT OF DIGITAL MARKETING STRATEGIES ON IMPROVING COMPETITIVE ADVANTAGE: THE MEDIATING ROLE OF THE BRAND, A CASE STUDY OF THE OPINIONS OF A SAMPLE OF EMPLOYEES AT AL NARJIS CONTRACTING COMPANY - Dhaha Nizar Talib Muhammad; Dr. Profe. Safaa Mohammed Hadi Hashim (Scholar Express Journals, 2025)
The study aimed to analyze and understand the impact of digital marketing strategies on improving sustainable competitive advantage, focusing on the role of branding as an intervening variable. The field problem of the study was the company's lack of commitment to implementing digital marketing strategies that aim to activate modern methods of communicating with customers to market products. To achieve the study's objectives, a descriptive analytical approach was used to interpret variables, analyze information, and obtain advanced results. Accordingly, an electronic questionnaire was designed consisting of three variables. The sample consisted of (150) employees, including specialists in the company from senior and middle management who were able to respond. The data was analyzed using statistical programs (SPSSv26, Amos, Smartpls). To achieve the study's objectives, the study relied on the descriptive analytical approach in the practical aspect of the study to test hypotheses by examining the impact of the relationship between digital marketing strategies and sustainable competitive advantage, with branding as an intervening variable. The importance of this study lies in the fact that digital marketing strategies represent the language of the modern era, contributing to strengthening a company's competitive position in a challenging competitive environment fraught with rapid technological changes.
Keywords: digital marketing; digital marketing strategy; sustainable competitive advantage